Rußlands Ratifikation des Kyoto-Protokolls ein kritisches Plädoyer - Joachim Schwerd (Hamburg Institute of International Economics (HWWA), 2003)
At the beginning of december 2003 the nineth conference of the parties (COP) of the UN framework convention on climate change (Rio declaration 1992) will take place. This meeting is crucial as it depends only on russias ratification to get the Kyoto protocol started soon. This paper reflects the current state of the protocol and highlights the particular features of COP 9, e.g. the double ratification hurdle, which - as a technical speciality of the protocol - was suitable to strengthen russias position in these negotiations up to now. It will be discussed, why russia shall comply with the protocoll for ist mere own sake, too. Only one of the flexible Kyoto instruments is considered hereby: emissions trading. Two arguments are used for making the point, that it is in russias interest to enable the protocolls functioning: only by compliance russia could silver its hot air; another strand of thinking refers to the accretion of russias natural gas exports. Beyond that dynamic efficiency gains of emissions trading are highlighted in general.
Keywords: F18; D90; D78; B52; 330; Kyoto protocoll; emissions trading; dynamic efficiency; russia; Klimaschutz; Umweltabkommen; Umweltzertifikat; Kosten-Nutzen-Analyse; Russland